Stenotrophomonas maltophilia responds to exogenous AHL signals through the LuxR solo SmoR (Smlt1839) - Martínez, Paula; Huedo, Pol; Martinez-Servat, Sònia; Planell, Raquel; Ferrer-Navarro, Mario; Daura, Xavier; Yero, Daniel; Gibert, Isidre (Frontiers in Cellular and Infection Microbiology, 2015)
Quorum Sensing (QS) mediated by Acyl Homoserine Lactone (AHL) molecules are probably the most widespread and studied among Gram-negative bacteria. Canonical AHL systems are composed by a synthase (LuxI family) and a regulator element (LuxR family), whose genes are usually adjacent in the genome. However, incomplete AHL-QS machinery lacking the synthase LuxI is frequently observed in Proteobacteria, and the regulator element is then referred as LuxR solo. It has been shown that certain LuxR solos participate in interspecific communication by detecting signals produced by different organisms. In the case of Stenotrophomonas malotphilia, a preliminary genome sequence analysis revealed numerous putative luxR genes, none of them associated to a luxI gene. From these, the hypothetical LuxR solo Smlt1839, here designated SmoR, presents a conserved AHL binding domain and a helix-turn-helix DNA binding motif. Its genomic organization –adjacent to hchA– indicate that SmoR belongs to the new family “LuxR regulator chaperone HchA-associated”. AHL-binding assays revealed that SmoR binds to AHLs in-vitro, at least to oxo-C8-homoserine lactone, and it regulates operon transcription, likely by recognizing a conserved palindromic regulatory box in the hchA upstream region. Supplementation with concentrated supernatants from Pseudomonas aeruginosa, which contain significant amounts of AHLs, promoted swarming motility in S. maltophilia. Contrarily, no swarming stimulation was observed when the P. aeruginosa supernatant was treated with the lactonase AiiA from Bacillus subtilis, confirming that AHL contributes to enhance the swarming ability of S. maltophilia. Finally, mutation of smoR resulted in a swarming alteration and an apparent insensitivity to the exogenous AHLs provided by P. aeruginosa. In conclusion, our results demonstrate that S. maltophilia senses AHLs produced by neighbouring bacteria through the LuxR solo SmoR, regulating population behaviours such as swarming motility.